Early response of understory vegetation to wood ash fertilization in the sub boreal climatic zone of British Columbia - Saskia C. Hart; Hugues B. Massicotte; P. Michael Rutherford; Ché M. Elkin; Bruce J. Rogers (The Forestry Chronicle, 2019)
Wood ash can be used as a soil amendment in forest ecosystems to alleviate nutrient loss, ameliorate soil acidity, increase tree growth, and reduce landfilled waste. Two hybrid spruce (Picea glauca X engelmannii) plantations in interior British Columbia were treated with two types of bioenergy-produced wood ash (high carbon boiler ash and low carbon gasifier ash) with or without nitrogen fertilizer in a two-way factorial block design. Ash and nitrogen treatments were applied to 8.0 m radius plots at a rate of 5000 kg ha-1 loose ash (dry basis), and 100 kg N ha-1 of urea in pellet form. Changes in understory vegetation cover were observed. There was a significant (p<0.05) effect of nitrogen and wood ash plus nitrogen application on understory vegetation community composition, with nitrogen application having the greatest effect. Discriminant function analysis indicated a differential response of species group to ash/ nitrogen treatments, though the effect size was small. We conclude that short-term changes to understory vegetation are minimal when these two ashes were applied at a rate of 5000 kg ha-1. Continued monitoring will determine if any long-term effects become apparent with time.